Estimasi Jasa Ekosistem Terumbu Karang di Pulau Mapur Kabupaten Bintan Kepulauan Riau: Estimation of Coral Reef Ecosystem Services on Mapur Island, Bintan Regency, Riau Islands - Rindani, Mersa; Wahyudin; Khairul Hafsar (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2024)
Mapur Island has a total area of 1,046.29 hectares, which it located at east part of Bintan Island. Mapur Island has the potential of coral reefs that are directly utilized by fishermen of Mapur Island (fishing ground) and the beautiful of coastal waters that are to be used tourisms activities such as snorkeling and diving. The study aims to identify coral reef ecosystem services in Mapur Island, Bintan Regency, Riau Islands and to estimate the economic value of coral reef ecosystems in Mapur Island, Bintan Regency. on January – February 2022 Mapur Island, Bintan Regency. Research using methods is a mixed method, combining two quantitative and qualitative research methods. Determination of respondents using a simple random method of Simple Random Sampling. This research was procedured by three stages, namely preparation, implementation and data processing. Data were analyzed in the form of direct use value, indirect use value, option value, and exitence value, total economic value (Total Economy Value). The results showed that the kind of the benefits of coral reef ecosystem services in the Mapur Island, Bintan Regency, Riau Islands, where it obtained 4 benefits: Direct used benefits; indirect used benefits; the benefits of choice; the benefits of existence. The results of the total economic value of coral reef ecosystems on Mapur Island, Bintan Regency with The area of 1,046.29 ha as big as IDR.1.010.753.105.005 year. With direct used benefits of IDR.897.077.366.884 year, indirect used benefits of coral reef ecosystems of IDR.8.740.788.790 year, elective benefits of IDR.99,104,588,800 year, and existence benefits of IDR.100,600,531 year.